Characterization of Root and Foliar-Applied Iron Oxide Nanoparticles (α-Fe2O3, γ-Fe2O3, Fe3O4, and Bulk Fe3O4) in Improving Maize (Zea mays L.) Performance - Yousaf Nauman; Ishfaq Muhammad; Qureshi Hassan Ali; Saleem Atif; Yang Haofeng; Sardar Muhammad Fahad; Zou Chunqin (MDPI, 2025)
Iron (Fe) oxide nanoparticles (NPs) improve crop growth. However, the comparative effect of root and foliar-applied different sources of Fe oxide NPs on plant performance at morphological and physiological levels still needs to be discovered. In this study, we characterized the growth and physiological responses of hydroponic-cultured maize seedlings to four sources of Fe (i.e., α-Fe2O3, γ-Fe2O3, Fe3O4 NPs, and bulk Fe3O4) and two application methods (root vs. foliar). Results showed that Fe concentration in root and shoot increased by elevating the level of NPs from 100 mg L−1 to 500 mg L−1. Overall, the responses of maize seedlings to different sources of Fe oxide NPs were as follows: Fe3O4 > γ-Fe2O3 > α-Fe2O3 > bulk Fe3O4. The application of Fe at concentrations ranging from 100 mg L−1 to 500 mg L−1 had no significant effects on various growth parameters of maize, including biomass, chlorophyll content, and root length. Iron oxide NPs increased the plant biomass by 23–37% by root application, whereas it was 5–9% by foliar application. Chlorophyll contents were increased by 29–34% and 18–22% by foliar and root applications, respectively. The non-significant response of reactive oxygen species (i.e., superoxide dismutase, catalase, and peroxidase) suggested optimum maize performance for supplementing Fe oxide NPs. A confocal laser scanning microscope suggested that Fe oxide NPs entered through the epidermis and from the cortex to the endodermis. Our results provide a scientific basis that the root application of Fe3O4 at the rate of 100 mg L−1 is a promising approach to obtain higher maize performance and reduce the quantity of fertilizer used in agriculture to minimize environmental effects while improving crop productivity and quality. These findings demonstrated the tremendous potential of Fe NPs as an environmentally friendly and sustainable crop approach.